Foreign Outposts of Colleges and Universities - Kinser, Kevin; Lane, Jason (International Higher Education, 2012)
Understanding the phenomenon of international branch campuses requires expanding our understanding of the various ways universities operate foreign educational outposts. A wide variety of transnational activity exists that represents intriguing variations on the typical branch campus form.